Standard handbook of environmental engineering - Corbitt, Robert A. (McGraw-Hill, 1990)
The handbook is a comprehensive manual on the principle and practice of environmental engineering chapters are provided on the most significant technical aspects of air quality control, water supply, wastewater disposal, and solid waste management. Also, individual chapters are provided in stormwater and hazardous waste management; these two disciplines are of current notariety and will become even more important in the years ahead.